Potensi Pendapatan Retribusi Parkir Dari Sudut Pandang Juru Parkir Liar (Studi Kasus di Kecamatan Padang Timur) - Muhammad Arif Fikrian; Charolie Cheisviyanny; Vita Fitria Sari (Universitas Negeri Padang, 2022)
This research is based on the phenomenon of a large retribution loss in the city of Padang. The purpose of this study is to calculate the potential levies and excavations that are felt as parking attendants from parking activities in the Padang Timur District, Padang City. This research is an descriptive-exploratory research. Data was collected by means of interviews, observation and documentation (triangulation). The sample in this study is a parking attendant who is in the District of East Padang. The results of this study found that (1) East Padang Subdistrict has a large potential for parking fees (2) The deposit system that applies in East Padang District is still unfair for parking attendants.Keywords: parking attendant, parking attendant justice, parking activity management, parking retribution potential